Analysis of Financial Audit and Shariah Audit at the National Amil Zakat Agency (BAZNAS) Madiun City - Ahmad Kudhori; Hedi Pandowo (Politeknik Negeri Madiun, 2022)
The existence of groups or institutions engaged in the collection and distribution of zakat, infaq and alms funds has recently increased in number. Most of them are still not officially registered at the Ministry of Religion. As a form of accountability to mustahik, it is mandatory to carry out a financial audit and of course also a sharia audit. The Baznas of Madiun City as one of the amil zakat bodies established by law is also inseparable from these obligations, which have been financially audited by a public accounting firm and also a sharia audit by the Inspectorate General of the Ministry of Religion of the Republic of Indonesia. The purpose of this study was to analyze the problems in the findings of the sharia audit conducted by the Inspectorate General of the Ministry of Religion of the Republic of Indonesia with a financial audit conducted by the Public Accountant Office as a comparison at Baznas Madiun City. The research method uses a descriptive qualitative approach, collecting data by observation, documentation and interviews, in this case carried out with the leaders and implementers of the Madiun City Baznas. The results of this study are that there are several differences in the concept of assessment between the results of the sharia audit findings and the audit results from the Public Accounting Firm.